Concentration‐dependent effects of proinflammatory cytokines on barrier function and tight junction protein expression in brain microvascular endothelial cells and the hypothermic and hyperthermic effects on tight junction protein expression. Issue 1 (28th September 2022) - Matsui, Tomohiro; Mochiduki, Yuji; Yoshida, Yusuke; Nitta, Takenori
Abstract: Objective: The mechanisms underlying therapeutic hypothermia, which protects neurons following severe brain damage, are only partially understood. We previously demonstrated that hypothermia reduced, whereas hyperthermia augmented, the release of tumor necrosis factor (TNF)‐α and interleukin (IL)‐17. Cerebral ischemia causes the loss of the blood–brain barrier (BBB) integrity, thereby increasing cerebral vascular permeability, which directly contributes to vasogenic edema, hemorrhagic transformation, and increased mortality. Brain microvascular endothelial cells (BMVECs) are a major component of BBB and tight junction proteins (TJPs) in these cells maintain the BBB integrity. In this study we determined the mechanisms underlying this treatment by measuring the effects of TNF‐α and IL‐17 on BMVEC barrier function and TJP expression in BMVECs, and by evaluating the effects of hypothermia and hyperthermia on TJP expression. Methods: The barrier function of BMVECs was evaluated by measuring transepithelial electrical resistance (TEER). The expression of several TJPs, such as claudin‐5 and junctional adhesion molecule (JAM)‐B, was measured at the mRNA and protein levels using real‐time polymerase chain reaction and immunocytochemistry, respectively. Results: TNF‐α and IL‐17 decreased TEER values, and TNF‐α decreased claudin‐5 and JAM‐B mRNA and protein levels, whereas IL‐17 decreased JAM‐B mRNA and protein levels, and all of these effects were concentration‐dependent. Compared with normothermia, claudin‐5 and JAM‐B proteins were not affected by hypothermia, whereas JAM‐B protein was reduced by hyperthermia. Conclusion: The hypothermic suppression of TNF‐α and IL‐17 release may contribute to the maintenance of BBB function by ameliorating the decrease of TJP(s). In contrast, hyperthermia may decrease barrier function through a decrease in JAM‐B expression. However, the contribution of changes in the JAM‐B expression to the barrier function of BMVECs remains to be clarified.